A Precoding Scheme Based Game Theory for Cooperative MIMO System - Hao, Dong Lai; Chen, Ying Mei; Zhang, Hong (Applied mechanics and materials, 2012)
This paper considers a tradeoff between maximizing the user’s signal interference noise ratio and minimizing interference leakage in preprocessing for multi-cell MIMO system. A sub-optimal precodingalgorithm based on game theory is proposed to deal with it. A game-based algorithm mathematics model is constructed and interference pricing function is also introduced in the solution to the precoding vector by Lagrange equation. Implement step of the proposed algorithm is also summarized in the paper. Finally in simulation the proposed algorithm is compared with conventional algorithms and convergence of utility function is also discussed. The simulation results show that the proposed algorithm provide improvement over existing schemes.